Foundry technology - Beeley, Peter R. (Butterworth Heinemann, 2001)
Foundry Technology brings together basic metal casting phenomena, foundry techniques and product characteristics in a single work of reference. Peter Beeley was a foundry manager before he became a senior lecturer in metallurgy, and subsequently maintained continuous links with the castings industry and associated research activities and publications. His book is designed to serve as a bridge between the study of the basic principles of metal founding and their application in the producing and user industries. A particular aim of Foundry Technology is to assist engineers and engineering students in appreciating the role of castings in design and materials selection. Orthodox and specialized casting processes, and both ferrous and non-ferrous founding are considered on a comparative basis, and the place of castings in design is critically examined and related to other products. The revised edition takes account of the main changes in casting processes and products since the publication of the original edition in 1972. While retaining treatments of basic aspects of molding, solidification, cast structures and feeding, newer developments in modeling and rapid prototyping are reviewed, together with quality, environmental, health and other issues of growing importance. New edition of well-known book. Fully updated with latest technology.